ANALISIS PENGARUH PERISTIWA PENGUMUMAN KABINET INDONESIA BERSATU JILID DUA TAHUN 2009 DAN KABINET KERJA TAHUN 2014 TERHADAP REAKSI HARGA SAHAM (STUDI KASUS SAHAM LQ 45 DI PT. BURSA EFEK INDONESIA) - Izzati, Emmi; Jati, Agung Nugroho (Kiat Bisnis, 2014)
The purpose of this research is to investigate the information content of Cabinet Indonesia Bersatu Jilid Dua and Cabinet Kerja announcement. Another purpose of this research is to examine the effect of Kabinet Indonesia Bersatu Jilid Dua and Kabinet Kerja announcement toward decision making of the investor in doing capital market transaction based on stok cost.This study is an event study, which observed the abnormal return and trading volume activity 5 day before, event date, and 5 days after the date of Cabinet announcement the research based on the secondary date collected from Indonesia Stok Exchange and Date Center Capital Market. The date that used in this research were the daily closing stock price, abnormal return daily, trading volume and share trade. Sample of this research were stocks listed in the LQ 45 at Indonesia Stock Exchange.The results of the analysis show the following (1) the two Cabinet announcement possess information content that couse the stock exchange to react in Cabinet Indonesia Bersatu Jilid Dua announcement there were significantly positive abnormal return on day 1 after and significanty negative abnormal return day 3 and day 4 after the announcement. In Cabinet Kerja the stock exchange gave significanty on day 2 before and day 2 after announcement. (2) the reaction given by the investor toward the two announcement are not relatively different, as the average, abnormal return in Kabinet Indonesia Bersatu Jilid Dua did not statistically have any significant differences compared to the average abnormal return in Kabinet Kerja. Keywords : stock cost, announcement Kabinet Indonesia Bersatu Jilid Dua and Kabinet Kerja, abnormal return and trading volume activity